PENERAPAN METODE DRILL SEBAGAI STRATEGI PENINGKATAN KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR: APPLICATION OF DRILL METHOD AS A STRATEGY TO IMPROVE THE COUNTING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Lusyana, Evvy; Fahera, Nisa (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2025)
Having numeracy skills from an early age is an important aspect as an initial foundation for developing students' cognitive development and academic success in the future. The aim of this research is to improve elementary school numeracy skills through the application of the Drill Method. Basic skills in learning mathematics through the ability to count are very important. The problem that researchers found was that students' numeracy skills were below the Minimum Completeness Criteria (KKM). This research is a descriptive qualitative research type of filed research. The research subjects were all 20 class V students at SDN Kandangsapi 3 Jenar. Data collection techniques through observation, interviews and documentation. Data validity uses data triangulation and methodology. The research results show that . Based on this information, it can be concluded that the application of the drill method is able to improve students' numeracy skills, because through this method students practice consistently in solving problems, so that students' numeracy skills are sharpened and deepened with the percentage of completeness increasing to 75% from previously only 40%.